First-principles Study of Magnetism and Electronic Structure of LixFePO4 - D, Odkhuu; T, Tsevelmaa; N, Tsogbadrakh; S. C., Hong (Scientific transaction of the National University of Mongolia. Physics, 2022)
LiFePO4 have attracted a great interest as a cathode material for Li rechargeable batteries. In this study we evaluated the magnetism emphasizing on magnetization axes and electronic structures of the olivine phases of LixFePO4 (0 x 1) by means of density-functional theory. We show that the insertion/extraction of lithium affects slightly the magnetic moment of Fe, but the spin orientations in antiferromagnetic ground state are found to be noteworthy. The easy magnetization axis of FePO4 is along [010], whereas it is on [001] for LiFePO4, in consistent with an experiment. The use of exchange-correlation U parameter in the electronic structure calculations describes well the observed insulating characters of FePO4 and LiFePO4.